From Usable to Useful Assessment Knowledge and Evaluation - Eva L. Baker (Universidad de Navarra, 2009)
In this article contrasts are made between usable and useful knowledge. Usable knowledge represents knowledge that someone finds pertinent. Useful knowledge has a function and can lead to specific action. The applications to educational assessment and evaluation are clear in that much assessment knowledge is developed at a level that is nominally usable, but provides no real guidance in the improvement of learning. Knowledge management through the measurement of social and organizational capital is suggested as a strategy to augment accountability policies based exclusively on test scores. This approach would work as a way to set targets and monitor the development of schools as an institution, responsible for performance by adults and students that extend beyond measured performance.